Understanding motivational differences in mathematics: a demographic perspective - Marco Hernández-Martínez; Miguel Posso-Yépez; Gabriela Arciniegas-Romero; Jaime Rivadeneira-Flores; Miguel Narváez-Pinango; Fernando Placencia-Enríquez (Cogent Education)
Motivation toward mathematics may vary depending on sociodemographic factors, such as gender, age and ethnicity. This study aims to determine the correlation level between motivation toward mathematics and students’ gender, age and ethnicity in Upper Basic Education. Additionally, it seeks to identify whether there are significant differences in motivation across various groups within these sociodemographic variables. This correlational and descriptive study employed the Astudillo-Villalba et al. test, consisting of 31 indicators distributed across two dimensions: intrinsic and extrinsic motivation. The study population included 25,005 Basic Education students from Imbabura Province (Ecuador), with a probabilistic sample of 2032 students who completed the instrument. Results indicate that motivation toward mathematics is associated with gender and age (p value > 0.05); moreover, there are significant differences in motivation among independent sample groups of gender and age. It is concluded that sociodemographic factors must be considered in motivating students toward studying mathematics to enhance teaching and learning processes.